Assessing the Weed-Suppressing Potential of Cotton Chromosome Substitution Lines Using the Stair-Step Assay - Mary Gracen Fuller (MDPI AG, 2021)
Palmer amaranth is a problematic common weed species, especially in cotton. With the wide use of chemical herbicide and herbicide-tolerant transgenic cotton lines, Palmer amaranth populations have developed tolerance to commonly used herbicides. It is imperative to develop alternative weed control methods to slow the evolution of herbicide-resistant weed populations and provide new strategies for weed management. Eleven chromosome substitution (CS) cotton lines (CS-B26lo, CS-T17, CS-B16-15, CS-B17-11, CS-B12, CS-T05sh, CS-T26lo, CS-T11sh, CS-M11sh, CS-B22sh, and CS-B22lo) were screened for weed-suppressing abilities in this study. The cotton lines were tested using the established stair-step assay. Height (cm) and chlorophyll concentration (cci) were measured for each plant in the system. The most significant variation in Palmer amaranth height reduction among the CS lines was observed 21 days after establishment. CS-B22sh (76.82%) and T26lo (68.32%) were most effective in reducing Palmer amaranth height. The cluster analysis revealed that CS-B22sh, and CS-T26lo were clustered in one group, suggesting similar genetic potential with reference to Palmer amaranth growth and development. CS-B22sh showed novel genetic potential to control the growth and development of Palmer amaranth, a problematic weed in cotton fields. Future experimentation should implement more parameters and chemical testing to explore allelopathic interactions among CS lines and Palmer amaranth.